MANAGEMENT STRATEGY: School Financial Management Strategies During the Covid-19 Pandemic - Muhammad Solikhin; Erni Munastiwi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The success of financial management during the Covid-19 pandemic is the role of school strategic management to prepare planning, organizing, controlling, and directly in school financial management. The research aims to examine educational institutions' financial management strategies in upper secondary education units. This type of research is field research with qualitative methods of case studies at MAN 2 Yogyakarta. The respondents of this study are the Principal, committee, and financial manager of the school. The data collection process is carried out by making observations, interviews, and documentation. The data analysis researchers use with the Miles and Huberman Models is condensation, data presentation, and inference/verification. The results of this study show that the strategy carried out by the Principal in managing school finances during the Covid-19 pandemic is an evaluation of budget, fund efficiency, and efficiency of program implementation through the stages of the financial management process. The strategy then, in the policy in the form of a 30% cut in SPP costs and the temporary elimination of visit transportation costs, waiver of payment time extension for parents whose businesses are affected by Covid-19, a 10% cut to school activity budget.